Transaction Cost Theory in Contemporary Accounting and Governance Research: A Systematic Literature Review (2020–2025) - Lydia Yuntika; Sambas Ade Kesuma; Iskandar Muda; Firman Syarif (Indo Publishing, 2025)
Transaction Cost Theory (TCT) has long served as a foundational lens for explaining organizational coordination, governance mechanisms, and the role of accounting systems in mitigating information asymmetry and opportunistic behavior. This study systematically reviews contemporary research published between 2020 and 2025 that applies TCT within the domains of accounting and governance. Using a structured search and screening procedure based on the Scopus database, 18 peer-reviewed open-access journal articles were identified as directly relevant to TCT applications in accounting and governance. The findings show that recent scholarship continues to rely on TCT to explain governance choices, contractual arrangements, internal control design, cost efficiency, and decision-making under uncertainty. Moreover, digital transformation, inter-organizational collaboration, and institutional pressures have substantially shaped the way transaction costs are conceptualized in modern organizations. This review synthesizes key themes, methodological patterns, and theoretical contributions, while outlining several avenues for future research, particularly in areas related to digital governance, data-driven control systems, platform economies, and hybrid organizational forms. Overall, the review demonstrates that TCT remains theoretically robust and practically relevant for contemporary accounting and governance research.